Financial Literacy and Financial Education: An Overview - Tim Kaiser; Annamaria Lusardi (Center for Economic Studies and ifo Institute (CESifo), 2024)
This article provides a concise narrative overview of the rapidly growing empirical literature on financial literacy and financial education. We first discuss stylized facts on the demographic correlates of financial literacy. We next cover the evidence on the effects of financial literacy on financial behaviors and outcomes. Finally, we review the evidence on the causal effects of financial education programs focusing on randomized controlled trial evaluations. The article concludes with perspectives on future research priorities for both financial literacy and financial education.
Keywords: G53; D14; 330; financial education; financial literacy; financial behavior